Preincision Adjunctive Prophylaxis for Cesarean Deliveries: A Systematic Review and Meta-analysis. Issue 3 (24th September 2022) - Markwei, M.T.; Babatunde, I.; Rathi, N.; Fan, C.; Prah, M.-A.; Joo, J.; Hackett, L.; Soper, D.E.; Goje, O.
Abstract : ( Am J Obstet Gynecol . 2021;225:382.e1–382.e13) Surgical site infections (SSI) occur after 2% to 7% of cesarean deliveries. While the administration of preincision beta-lactam antibiotics is recommended, there is a high rate of SSIs following cesarean delivery. Adjunctive prophylaxis, or the administration of a second antibiotic, has been shown to decrease postcesarean SSI rates. Azithromycin has been the adjunctive prophylaxis drug of choice in addition to cefazolin. As azithromycin was more difficult to obtain during the COVID-19 pandemic, clarithromycin has been used in its place. This study aimed to evaluate the use of preincision cefazolin with macrolides or metronidazole compared with cefazolin alone in terms of decreasing the incidence of SSIs following cesarean delivery.